The Effect Of Entrepreneurship Education And Industrial Work Experience On Entrepreneurial Readiness, With Self-Efficacy As A Moderating Variable, Among Vocational High School Students - Dininggar Indah Shafira; Susi Indriani; Achmad Fauzi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The purpose of this study is to analyze and discusses the effect of entrepreneurship education and industrial work practices on students' entrepreneurial readiness This research uses primary data collected from the distribution of Likert scale questionnaires to 155 respondents who are selected using probability sampling out of a total population of 252 students class XII for the period 2025–2026. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach using SmartPLS 4.0 software. We have opted for this method because it allows us to fully analyze the links of causation between the variables, covering both the measurement model (outer model) and the structural model (inner model). The results demonstrate that entrepreneurship education has a positive and significant effect on entrepreneurial readiness while industrial work practices do not have a influence of legitimate significance to commercial sense of readiness. In addition, based on the moderation test results showed that self-efficacy is moderating in the relationship between entrepreneurship education and entrepreneurial readiness, also industrial work practices against entrepreneurial readiness. The main practical implications of this study highlight that self-efficacy is a very important key to converting entrepreneurship knowledge and practical experience into real entrepreneurial readiness in students.